The devil is in the details: Transposable element analysis of the Tasmanian devil genome. (2nd January 2016) - Nilsson, Maria A.
ABSTRACT: The third marsupial genome was sequenced from the Tasmanian devil ( Sarcophilus harrisii ), a species that currently is driven to extinction by a rare transmissible cancer. The transposable element (TE) landscape of the Tasmanian devil genome revealed that the main driver of retrotransposition theL ongIN terspersedE lement 1 (LINE1) seem to have become inactivated during the past 12 million years. Strangely, theS hortIN terspersedE lements (SINE), that normally hijacks the LINE1 retrotransposition system, became inactive prior to LINE1 at around 30 million years ago. The SINE inactivation was in vitro verified in several species. Here I discuss that the apparent LINE1 inactivation might be caused by a genome assembly artifact. The repetitive fraction of any genome is highly complex to assemble and the observed problems are not unique to the Tasmanian devil genome.